2020
DOI: 10.3389/fonc.2020.551255
|View full text |Cite
|
Sign up to set email alerts
|

A New Model for Predicting Hypothyroidism After Intensity-Modulated Radiotherapy for Nasopharyngeal Carcinoma

Abstract: Objectives: To develop a model that can predict the risk of hypothyroidism (HT) after intensity-modulated radiotherapy (IMRT) for nasopharyngeal carcinoma (NPC), and to accordingly recommend dose constraints. Materials and Methods: NPC patients treated between 2011 and 2015 were retrospectively reviewed. HT was defined by an abnormally high level of thyrotropin. The dosimetry parameters V x (percentage of thyroid volume receiving more than x Gy of radiation) and V a,b (percentage of thyroid volume receiving >a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…Radiotherapy-induced hypothyroidism (RHT) is one of the common late-stage toxic reactions in patients who have received cervical radiotherapy, and its incidence is as high as 20%–40% ( 1 3 ), which is higher than the incidence in the normal population. The occurrence of hypothyroidism after radiotherapy in most studies was concentrated within 5 years after radiotherapy, and it generally reached a peak approximately 1 to 3 years after radiotherapy ( 4 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Radiotherapy-induced hypothyroidism (RHT) is one of the common late-stage toxic reactions in patients who have received cervical radiotherapy, and its incidence is as high as 20%–40% ( 1 3 ), which is higher than the incidence in the normal population. The occurrence of hypothyroidism after radiotherapy in most studies was concentrated within 5 years after radiotherapy, and it generally reached a peak approximately 1 to 3 years after radiotherapy ( 4 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…The crude incidence of post-radiation hypothyroidism exceeded 30 % in 11 studies in which the median follow-up duration was longer than 3 years [10,14,17,18,[20][21][22][23][24]. Sixteen of 29 studies (55 %) reported the median time to hypothyroidism [8,11,13,15,17,[20][21][22]24,26,28,[30][31][32][33]37]. Hypothyroidism occurred at a median of 1.1 years (range, 0.7-3.1 years) after head and neck radiotherapy.…”
Section: Incidence Of Post-radiation Hypothyroidismmentioning
confidence: 99%
“…The included studies were published from 2010 to 2021 across 13 countries, and all studies were observational in design. Nineteen studies provided comparative data on radiation dose-volume predictors (Table 1) [8,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27], while 10 studies reported radiation dosimetric nomograms or normal tissue complication probability (NTCP) models for post-radiation primary hypothyroidism (Table 2) [28][29][30][31][32][33][34][35][36][37]. The primary tumors were nasopharyngeal carcinoma (NPC), oropharyngeal carcinoma (OPC), and other sites in 41.4 % (12/29), 17.2 % (5/29), and 41.4 % (12/29) of the studies, respectively.…”
Section: Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations